Two-stage revision after total knee arthroplasty - Di Benedetto, Paolo; Di Benedetto, Enrico Daniele; Buttironi, Michele Mario; De Franceschi, D.; Beltrame, Alessandro; Gissoni, Renato; Cainero, Vanni; Causero, Araldo (Acta Biomedica Atenei Parmensis, 2017)
Background and aim of the work. Periprosthetic knee infection is a complication associated with prosthetic failure; incidence change from 0,4-2% of primary total knee replacement and 5,6% in revisions; incidence is increasing over the years. Two-stage revision is the technique used in chronic infection. Aim of the work is to check success rate in our data. Methods. We analyzed retrospectively data of patients who undergone two stage revision surgery between 01/01/2010 to 31/12/2015. We made a clinical and radiological control after 1, 3, 6, 12, 24 months and we evaluate the outcome in December 2016. Results. Between 2010 and 2015 we treated 45 patients with two-stage revision. Mean follow-up was 3,4 years. Success rate is 89,9%. We had failure in 5 patients: everyone had knee surgery before first knee arthroplasty and Charlson Comorbidity Score was greater then 4 in 4 cases. Conclusions. Two stage revision can be considered a successful treatment in chronic periprosthetic knee infection. It has an optimal success rate, but it has some disadvantages as joint stiffness and pain in the interval between stages. This is a technique with two major surgery procedure with associated morbidity, discomfort, cost and prolonged stay in hospital.